Higher Education Across Europe: Contemporary Missions for Historical Institutions - Tamar Groves; Ana Cuevas Badallo (FahrenHouse, 2016)
Universities may be old institutions, but at the beginning of the 21st century they find themselves assuming new roles, such as developing the economy, contributing to social integration, fomenting cultural diversity, defending human rights, guaranteeing regional development and even protecting the environment. The complex combination of neoliberal economy, globalization and the emergence of the knowledge society has not undermined their position, on the contrary, it has led to their expansion. We thus sketch very briefly the varied characteristics of European universalities today and outline the major challenges which they confront. Using a variety of case studies we look at processes of modernization and incorporation of new technologies, as well as attempts to redefine systems of evaluation and admission. We also discuss threats to their essence as autonomous research and teaching institutions, due to closer relations with the economy and its demands for highly qualified workers.